Book Review: Wedding of the Waters: the Erie Canal and the Making of a Great Nation. (20th October 2006) - Rhoades, Dawna L.
Wedding of the waters: the Erie Canal and the making of a great nation, by Peter L. Bernstein. New York, W.W. Norton & Company, 2005. ISBN 0-393-05233-8,